Topic-marking prepositions in Swedish: A corpus-based analysis of adpositional synonymy. Issue 2 (16th October 2014) - Granvik, Anton; Taimitarha, Susanna; Andersen, Gisle; Hardt, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> This study analyses the relationship between four near-synonymous Swedish prepositions, namely angående, beträffande, gällande and rörande, which are used to establish what we call a topic-marking relation, as in statens avtal angående finansieringen 'the agreement of the state regarding the financing'. By focusing on a single, loosely defined genre consisting of the written texts included in the Swedish PAROLE corpus, we address the question of what differences there are among these four prepositions, which intuitively seem highly similar and mutually interchangeable. In order to find out which contextual and grammatical factors might influence the choice of one preposition over the others, two complementary analyses were performed. First, a so-called collostructional analysis (see Stefanowitsch & Gries 2003, Gries & Stefanowitsch 2004) was performed on 791 cases of these prepositions found in the PAROLE corpus. Secondly, the corpus examples were annotated according to ten syntactic and four semantic criteria and a multinomial logistic regression analysis was performed on the annotated data set. The results show some tendencies pointing to differing usage patterns of the four prepositions. Beträffande stands out as the most frequent of them all and is also preferably used when no explicit head element is present, typically in sentence-initial position. Angående prefers words of communication while rörande is used when another topic-marking preposition is also present. On the other hand, neither of the two analyses leads to a clear distinction among the four prepositions, thus pointing to the fact that these topic-marking prepositions indeed constitute a fairly good case of adpositional synonymy, with few distinguishing factors separating one from the other.